Structural Behaviour of Reinforced Concrete (RC) Deep Beam with Web Opening Strengthened using Carbon Fibre Reinforced Polymer (CFRP) - Rahim, Nurul Izzati (Universiti Teknologi PETRONAS, 2018)
These days, construction is more towards the high-rise building and a deep beam is considered as one of the structure that always caught structural engineers’ interest as it is used as transfer girders, foundation pile caps as well as wall footings. The deep beam which having small span to depth ratio will transfer the external load to the support through compression action and it is said that the shear failure is most likely to happen in deep beam instead of normal beam. This experimental study aimed at examining the structural behaviour of the reinforced concrete (RC) deep beam having an opening strengthened using Carbon Fibre Reinforced Polymer (CFRP) in the shear zone. Total of 9 RC deep beams with opening and one without opening which acts as a control beam having a dimension of 2000mm x 130mm and 500mm in height were fabricated and tested at the lab to check for the structural behaviour such as failure mode, load-deflection behaviour, crack pattern of the beam. The beams were tested with two symmetrical loads, each located 850mm from the edges of the beam after the CFRP was attached around the opening.